4-[Bis(2-chloroethyl)amino]benzaldehyde - P. Seethalakshmi; C. Palanivel (IUCrData, 2017)
In the title compound, C11H13Cl2NO, the chloroethyl amino groups are twisted with respect to the amino group, with N—C—C—Cl torsion angles of −177.4 (4) and 179.2 (3)°. The carbonyl group lies in the plane of the benzene ring to which it is attached; torsion angles Car—Car—C=O are 0.1 (8) and −178.2 (5)°. In the crystal, C—H...Cl and C—H...O hydrogen bonds link the molecules, forming sheets parallel to (20-1). The sheets are linked by C—H...π interactions, forming a three-dimensional framework.